Analisis Faktor-Faktor Yang Dapat Mempengaruhi Kepuasan Serta Loyalitas Pelanggan Di Portal Belanja E-Commerce - Yvonne Wangdra; Realize Realize; Kiki Sumanti (Prosiding, 2022)
The purpose of this research is to determine 1. Effect of Work Discipline on Employee Performance Along with increasing human needs, in the modern era, internet and telecommunication technology are experiencing very rapid development. This is more or less a factor of cultural change in everyday life. In this information age era, electronic media has become an intermediary tool for doing business and communication. Starting from small to large entrepreneurs, many take advantage of the advancement of internet technology as a means of competing for their business. Many new business applications are present due to the internet. The world of electronic commerce (E-Commerce) has a wider scope than ordinary buying and selling transactions. When managing their business, companies usually use the internet as a tool to find information and promote the company. In addition, it can be used as a means of information and promotion, the internet can also be used as a process of buying and selling products, services and information online. The development of electronic commerce has also brought many changes in terms of business activities that have been carried out in the real world. This change is marked by the existence of several business activities that previously could only be carried out in the real world. Judging from the characteristics of the problem, this research includes causal-comparative research because this research has a causal relationship between two or more variables consisting of Customer Perceived Value, Service quality, Trust, and Customer satisfaction which in this case plays a role. as independent and customer loyalty as the dependent variable